PSIKOTIK DAN PEDOFILIA DALAM “MAK IPAH DAN BUNGA-BUNGA” KARYA INTAN PARAMADHITA: KAJIAN PSIKOLOGI SASTRA - Choirunnisa Salwa Tawakal (Faculty of Cultures and Languages UIN Raden Mas Said, 2022)
This study aimed at describing mental disorders (psychic) ​​experienced by two characters, Mak Ipah and Pemuda in “Mak Ipah dan Bunga-bunga” written by Intan Paramadhita. The two characters (protagonist and antagonist) of the short story were analyzed using psychoanalysis theory. The theory believes that human being is more influenced by the subconscious than the conscious. Like a psychotic patient with schizophrenia; the patient is unaware of his deviant behavior or pedophilia and only cares about his desire (affecting his sexual behavior) for children, which he considers as something natural. This study used qualitative-descriptive method. The research data were in the form of literary text (short story) that represents a person's mental disorder (the characters). The sources of resesarch data were from the narrative text of the short story